The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.14422
|View full text |Cite
|
Sign up to set email alerts
|

Fermented black rice bran extract inhibit colon cancer proliferation in WiDr cell lines

Abstract: The objective of this study was to find the best inhibition of WiDr colon cancer cells growth using Fermented Black Rice Bran (FBRB) extract and the mechanism of colon cancer inhibition by fermented rice bran. In this study, BRB was fermented by Rhizopus oligosporus (FBROLI), Rhizopus oryzae (FBRO), respectively, for 0, 24, 48, 72, and 96 h to analyze changes profile of phenolic content, total flavonoid, and antioxidant activity during fermentation. The result of elected fermentation and non-fermented (0 h) (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Previous studies also showed that EBRB is not toxic to HUVEC cells [10]. Moreover, a study showed that EBRB did not have the toxicity effect in Vero cells with an IC50 value of 1139.5 μg/mL [56]. Cytotoxicity is classified into four categories based on IC50 values.…”
Section: Cytotoxicity Assay Ebrb 'Sembada Hitam' On Vero Cellsmentioning
confidence: 99%
“…Previous studies also showed that EBRB is not toxic to HUVEC cells [10]. Moreover, a study showed that EBRB did not have the toxicity effect in Vero cells with an IC50 value of 1139.5 μg/mL [56]. Cytotoxicity is classified into four categories based on IC50 values.…”
Section: Cytotoxicity Assay Ebrb 'Sembada Hitam' On Vero Cellsmentioning
confidence: 99%
“…In recent years, with the in-depth study of the composition and structure of wheat bran, it has been found that wheat bran is rich in phenols which are beneficial to human health (Lee et al, 2020;Xu et al, 2018). Pathological studies show that these phenols have important functional properties and pharmacological effects, and have potential application value in the prevention of many degenerative diseases, such as obesity, cancer, diabetes, cardio-cerebrovascular diseases and so on (Safrida et al, 2022;Zhao et al, 2017). Phenols in wheat bran mainly exist in two forms: soluble free phenol and insolublebound phenol.…”
Section: Introductionmentioning
confidence: 99%